2019
DOI: 10.1111/cobi.13277
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with ivory trade regulations in the United Kingdom among traders

Abstract: Global demand for elephant ivory is contributing to illegal poaching and significant decline of African elephant (Loxondonta africana) populations. To help mitigate decline, countries with legal domestic ivory markets were recommended by the Convention on International Trade in Endangered Species of Wild Fauna and Flora to close domestic markets for commercial trade. However, implementing stricter regulations on wildlife trade does not necessarily mean compliance with rules will follow. Using an online questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Although social norms and values encourage businesses to operate in line with societal expectations, having controls is vital in promoting environmental sustainability practices. Controls indicate business managers' knowledge, confidence and familiarity with the existing environmental regulations (Harris et al, 2019). Martin et al (2013) indicated that border control fosters wildlife law enforcement.…”
Section: Controls and Environmental Sustainability Practicesmentioning
confidence: 99%
“…Although social norms and values encourage businesses to operate in line with societal expectations, having controls is vital in promoting environmental sustainability practices. Controls indicate business managers' knowledge, confidence and familiarity with the existing environmental regulations (Harris et al, 2019). Martin et al (2013) indicated that border control fosters wildlife law enforcement.…”
Section: Controls and Environmental Sustainability Practicesmentioning
confidence: 99%
“…Nijman & Shepherd, 2015). This issue has caused major debate among conservationists, reflecting that surrounding the trade in ivory and rhino horn (Bennett, 2015; Collins, Cox, & Pamment, 2017; Harris, Gore, & Mills, 2019). Nevertheless, successful conservation marketing campaigns and environmental education can shift social norms and increase compliance with local legislation (Salazar, Mills, & Veríssimo, 2019; Veríssimo & Wan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Contestants and breeders both stressed the importance of sourcing birds from particular locations, and promoting a strong cultural attachment to place (Kristianto & Jepson, 2011) . This issue has caused major debate among conservationists, reflecting that surrounding the trade in ivory and rhino horn (Bennett, 2015;Collins, Cox, & Pamment, 2017;Harris, Gore, & Mills, 2019).…”
Section: Informing Evidence-based Behaviour Changementioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the authors was to examine how widespread the illegal pangolin trade starting from Gabon is, what illegal trade routes were developed, how and effectively law enforcement detects illegal shipments, and what conservation measures and policy decisions may be needed to address the problem. An online questionnaire survey was conducted in the U.K. to assess the effectiveness of restrictive, and austerity provisions were implemented to curb illegal ivory trade domestically (Harris et al, 2019). The survey encompassed legal traders.…”
Section: Methodsmentioning
confidence: 99%